'Bebel spricht im Reichstage zum Etat'; at the right sitting: Singer and standing at the utmost right: von Vollmar - Mannich, Rudolf (1905)
'Bebel spricht im Reichstage zum Etat'; at the right sitting: Singer and standing at the utmost right: von Vollmar.